Increasing Critical Thinking Skills and Communication Skills in Science: Blended Learning Project - Eli Trisnowati; Fifit Firmadani (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This study aims to obtain an overview of improving students' critical thinking skills and communication skills whose learning activities use integrated blended learning of local wisdom. Learning activities are carried out by modifying blended learning stages, namely at the seeking information stage. The research subjects were 109 students of the 2nd semester of science education study program. The research was conducted using a quasi-experimental method with a pretest-posttest design. The instrument used was a multiple-choice test using an assessment rubric and an observation sheet. The research data were analyzed using multivariate analysis. The results showed that the improvement of students' critical thinking and communication skills with blended learning (treatment class) was more significant than students whose blended learning was not integrated with local wisdom. Keywords: blended learning, local wisdom, critical thinking skills, communication skills